Probabilistic quadratic programming model for Sewon-Bantul facultative ponds optimization. (June 2020) - Sunarsih; Sutrisno
Abstract: This article is addressed to show the result of a probabilistic mathematical model implementation in Sewon, Bantul facultative wastewater treatment pond to analyse the performance of the pond. The model was developed in a probabilistic quadratic optimization model and was solved by using probabilistic programming by using deterministic equivalent approach. LINGO 18.0 optimization software package was employed to do the computation. The optimization result was giving the optimal decision value for the wastewater volume that should be processed in the pond in order to gain the best performance and the storing time of the wastewater for each facultative pond. For each facultative pond, the load volume of the wastewater should be 1199.5 kg where the storing time is 13.2 day for the first pond, 13.24 day for the second pond, 25.59 day for the third pond and 30.30 day for the fourth pond. This optimal decision, then, can be used by the decision maker (WWTP operator) in order to optimize the performance of the treatment ponds.